PENGGUNAAN ARANG AKTIF DALAM KULTUR IN VITRO - Sri Hutami (Research Center for Biology-Indonesian Institute of Sciences, 2006)
Activated charcoal is commonly used as addition in tissue culture medium, which able to modify the composision. The effect of activated charcoal can observed in culture medium or in tissue development.Effect of activated charcoal in the medium are: 1) give a darkened environnment; 2) adsorption of undesirable/inhibitory substances; 3) adsorption of growth regulators and other organic compound; and 4) released of growth promoting substances which are beneficial to growth of in vitro culture.In tissue development activated charcoal can promote embryogenesis, androgenesis, root induction and inhibit callus formation. Fators affecting charcoal activity are:quality (depend on raw material and processing), density, purity, organic compound (affecting adsorptionn), temperature pH and type of solvent.